2001
DOI: 10.1093/bmb/58.1.89
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric HIV infection: correlates of protective immunity and global perspectives in prevention and management

Abstract: The impact of the HIV epidemic on child health globally is beginning to be appreciated. With the burden of new infections falling on young women, there is a skyrocketing number of AIDS orphans, and a rapidly increasing number of children infected via mother-to-child-transmission (MTCT). An estimated 600,000 new paediatric infections occur each year, of which some 1500/day (> 90%) occur in sub-Saharan Africa. But whereas children account for only 4% of those currently living with HIV infection, 20% of AIDS deat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
32
0
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 71 publications
0
32
0
4
Order By: Relevance
“…Early studies of perinatally infected children in developed countries before the era of highly active antiretroviral therapy (HAART) 3 indicated that a subset of children (ϳ25%) progressed very rapidly to AIDS (within 1 year). The median time to AIDS for the remaining 75% was ϳ7 years (2). However, a minority of HIV-1-infected infants remain clinically asymptomatic beyond childhood and into adolescence.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies of perinatally infected children in developed countries before the era of highly active antiretroviral therapy (HAART) 3 indicated that a subset of children (ϳ25%) progressed very rapidly to AIDS (within 1 year). The median time to AIDS for the remaining 75% was ϳ7 years (2). However, a minority of HIV-1-infected infants remain clinically asymptomatic beyond childhood and into adolescence.…”
mentioning
confidence: 99%
“…More specifically, infection with nef/long terminal repeat-deleted HIV-1 resulted in slower disease progression among recipients from the Sydney Blood Bank Cohort (3). Differences in MHC class Irestricted HIV-1-specific CD8 ϩ T cell responses variably impact on disease progression (2). These include maintenance of large expansions of oligoclonal or monoclonal memory CD8 ϩ T cells targeted toward multiple conserved HIV-1 epitopes in a significant proportion of long-term survivors (LTSs).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Curiosamente, todas essas respostas efetoras se perderam completamente em ambos os grupos de pacientes quando suas CMSPs foram cultivadas na presença do antí-geno viral (Env). Essa falta de resposta pode ser explicada pelo efeito inibidor das proteínas virais e/ou pela perda de clones específicos contra o HIV durante a progressão da infecção 24,25 , ou pelo fato de que a infecção viral afetou as linhagens de células T no timo e destruiu a capacidade de produção de clones anti-HIV, como descrito [11][12][13] . Esse achado experimental requer maiores investigações para identificar os mecanismos moleculares responsáveis por essa falta de resposta por parte das crianças infectadas pelo HIV frente ao antígeno viral (Env).…”
Section: Discussionunclassified
“…Em crianças, devemos considerar vários fatores: a relativa imaturidade imunológica, a destruição do timo mediada pelo HIV-1 em um momento de timopoiese ativa, e o compartilhamento de antígenos leucocitários humanos de classe I entre a mãe e o bebê [11][12][13] . Poucos estudos investigaram o estado funcional dos linfócitos T CD4+ e CD8+ em PRs e PLs 11 com o objetivo de estabelecer relações entre evolução clínica e aspectos imunológicos.…”
Section: Introductionunclassified